Understanding Water Transport in Polymer Electrolyte Fuel Cells Using Coupled Continuum and Pore‐Network Models1. Issue 6 (6th April 2016) - Medici, E. F.; Zenyuk, I. V.; Parkinson, D. Y.; Weber, A. Z.; Allen, J. S.
Abstract: Water management remains a critical issue for polymer electrolyte fuel cell performance and durability, especially at lower temperatures and with ultrathin electrodes. To understand and explain experimental observations better, water transport in gas diffusion layers (GDLs) with macroscopically heterogeneous morphologies was simulated using a novel coupling of continuum and pore‐network models. X‐ray computed tomography was used to extract GDL material parameters for use in the pore‐network model. The simulations were conducted to explain experimental observations associated with stacking of anode GDLs, where stacking of the anode GDLs increased the limiting current density. Through imaging, it is shown that the stacked anode GDL exhibited an interfacial region of high porosity. The coupled model shows that this morphology allowed more efficient water movement through the anode and higher temperatures at the cathode compared to the single GDL case. As a result, the cathode exhibited less flooding and hence better low temperature performance with the stacked anode GDL.